A vitreoretinal service. Issue 6693 (22nd July 1989) - Richardson, J.; Wood, C. M.; Mackay, L. J.; Gardner, E. S.
Abstract : Many serious disorders that threaten eyesight can now be treated with vitreoretinal surgery. As there was no regional facility for this treatment a service was developed to provide it. Among the first 100 patients treated over half had diabetic vitreoretinal disease. The remainder had ocular trauma (15), non-diabetic vasculopathy (10), rhegmatogenous retinal detachment (10), and miscellaneous disorders including diagnostic procedures (14). Sight was improved in most cases, 27 diabetic and 21 non-diabetic patients regaining navigating vision. Few patients were made worse: one only of the 49 non-diabetic patients and 12 of the 51 diabetic patients, and none whose vision was better than the ability to count fingers before operation. The many indications for this procedure, the size of the population that could benefit (an estimated minimum of 3800 operations per year in the United Kingdom in patients with diabetes alone), and the great potential benefit of the procedure all suggest the need for regional services. These would be cost effective in preventing blindness.